Academic adaptation to higher education for neurodivergent students (Revista Contexto & Educação, 2026)
The process of entering higher education brings changes in the lives of these individuals, an increase in the demand for studies, new interactions and responsibilities to reconcile. It's an important time for their psychological development, a change in identity towards an autonomous profile that can have an impact on the way they deal with the university environment. By evaluating these experiences among minority groups, such as neurodiverse ones, it is possible to analyze different ways of facing this new phase. Therefore, this study aims to identify the conceptions of neurodiverse students regarding their Academic Adaptation to higher education. This is a descriptive, cross-sectional, qualitative study in which 12 neurodiverse university students took part, using a Sociodemographic Questionnaire as well as a Semi-Structured Interview conducted via the Zoom platform. Data was collected by inviting participants to universities or social network groups. The data was analyzed using the software Interface de R pour les Analyses Multidimensionnelles de Textes et de Questionnaires (IRaMuTeQ). As a result, a dendrogram was generated with six classes: “Strategies for attention in classes”, “Support network at university”, “Impact of academic demands”, “Vocational expectations”, “Challenges in interpersonal relationships” and “Challenges in university spaces”. It is concluded that different adversities, both academic and personal, appear in the university experience of the neurodiverse, and that attention should be paid to promoting the adaptation of this type of student. The importance of a support network for better integration of these students at university is highlighted.
Keywords: Academic Adaptation; Neurodivergents; University Students; Minorities